(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2017)
The notion of tópos, conceived as a principle shared by a community, has a central place in the treatises of rhetoric from Greco-Roman antiquity. This concept is also relevant, we believe, in literary discourse and it allows to establish a connections between literature and rhetoric. While comparative literature tends to disassociate this notion from its persuasive function, we understand that the tópoi have a complex function in ancient comedy: the tópoi are literary motifs, but also adopt an argumentative purpose. Aristophanes’ comedy, in particular, advocates certain political ideas, using a series of tópoi, either in the form of statements or character types. The tópoi are then used in both oratory and comedy with persuasive purposes.